2011
DOI: 10.1007/s00198-011-1838-0
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 is independently associated with vascular calcification but not bone mineral density in patients at various CKD stages

Abstract: Our data suggest that plasma FGF23 is an independent biomarker of vascular calcification in patients with various CKD stages including early stages. The association between vascular calcification and FGF23 levels appears to be independent of BMD. It remains to be seen whether this association is independent of bone turnover and bone mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
138
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 40 publications
8
138
3
2
Order By: Relevance
“…These findings do not confirm the results of Desjardins et al (47) and Ureña et al (48) that FGF23 does not correlate with DXA BMD. This finding may be because of possible differences in patient populations and more importantly, the cross-sectional nature of these two studies.…”
Section: Discussioncontrasting
confidence: 78%
“…These findings do not confirm the results of Desjardins et al (47) and Ureña et al (48) that FGF23 does not correlate with DXA BMD. This finding may be because of possible differences in patient populations and more importantly, the cross-sectional nature of these two studies.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, among the mineral metabolites we tested, FGF23 was most strongly correlated with each inflammatory marker, and FGF23 but not PTH or phosphate was associated with greater odds for severe inflammation in multivariable models. Given the associations between inflammation, atherosclerosis, and vascular calcification (21), and that some studies have shown association between elevated FGF23 and calcification in CKD and ESRD (22,23), these results provide new insight into another potential mechanism underlying the strong associations between elevated FGF23, cardiovascular disease, and mortality. Further studies are needed to determine whether FGF23 might contribute to atherosclerosis and vascular calcification by stimulating inflammation or whether inflammation might contribute to the development of vascular disease through effects on FGF23.…”
Section: Discussionmentioning
confidence: 82%
“…In patients with CKD, PTH and FGF-23 are increased as a compensatory response to maintain the phosphate balance from the early stages of CKD (2)(3)(4)(5). It has recently been suggested that hyperphosphatemia and FGF-23 are risks for vascular calcification, CKD progression, and death (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%